Prevalence of Erosive-ulcerative Lesions of the Stomach and Helicobacter Pylori Infection in Patients with Ulcerative Colitis - N. A. Ponkratova; P. V. Pavlov; O. S. Shifrin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To assess the prevalence of erosive-ulcerative lesions of the gastric mucosa, as well as the frequency of Helicobacter pylori infection in patients with ulcerative colitis. Materials and methods. The study included 70 patients with ulcerative colitis. All patients, along with the standard examination using esophagogastroduodenoscopy, were diagnosed with regard to H. pylori infection: all 70 patients received a rapid urease test (RUT), 24 patients (34.3 %) had H. pylori DNA analyzed in feces, and 46 patients (65.7 %) had 13C labeled urea breath test. The study of H. pylori infection with RUT was carried out in 111 patients without inflammatory bowel disease, who formed the control group.Results. Endoscopic examination of patients with ulcerative colitis revealed inflammatory and erosive changes in the gastric mucosa. In 7.1 % of cases (5 out of 70 people), the erosion of the body stomach was detected, in 40.0 % of patients (28 out of 70) – erosion of the antrum. No effect of previous steroid therapy, as well as the high activity of ulcerative colitis on the frequency of the stomach erosive lesions (respectively, p = 0.433; p = 0.158) was detected. H. pylori infection was found in patients with ulcerative colitis significantly less frequently than in the control group (respectively, in 52.9 % (37 people out of 70) and 71.2 % of cases (79 people out of 111); p = 0.012). No relationship was found between H.pylori infection and the severity of the exacerbation of the underlying disease (p = 0.157).Conclusion. In patients with ulcerative colitis, erosive changes frequently found in the stomach do not correlate with the activity of the underlying disease. H. pylori infection is less common in patients with ulcerative colitis than in individuals not suffering from inflammatory bowel disease.